SHADING EFFECT ON COFFEE TREE IN FORMATION STAGE - Franco Júnior, Kleso Silva; Florentino, Ligiane Aparecida (Coffee Science - ISSN 1984-3909, 2019)
According to the Intergovernmental Panel on Climate Change, global warming is expected with temperature rise and changes in the rainfall in tropical regions, including soil warming, which may lead losses to perennial plants. This phenomenon causes researchers to search through science alternatives in order to minimize these impacts. The objective in this research was to evaluate the cultivation of different plants in a intercropping for the coffee tree shading and its influence on the seedlings establishment, development, coffee growth and the maintenance of lower soil temperatures. The experiment was carried out at the Santa Felicidade Site, Campestre - municipality - South of MG , located at 21 ° 43’ 12 “South and 46 ° 14’ 46” West at an altitude of 1.106 meters. The cultivar used was the Catuai IAC 144, was intercropped with the following species: maize (Zea mays L.), guandu (Cajanus cajan L.), crotalaria (Crotalaria spectabilis L.), mucuna (Stizolobium aterrimun) and control without any intercrop, totaling five treatments. The plants sowing for shading was performed using a manual planter and the planting was done in 4 plots per treatment, totaling 20 experimental units in a randomized block design with 14 coffee plants per plot. The 10 central plants were analyzed. At the end of the experiment, the following characteristics were evaluated: seedlings establishment, growth in height, average length of plagiotropic branches, number of internodes in plagiotropic branches, coffee canopy and soil temperature. The data were statistically interpreted by means of variance analysis. The means were grouped by the Scott Knott test at 5% probability using the statistical software SISVAR®. According to the results obtained the shading plants in intercropped with the coffee tree managed in the post-planting and first-year phases contributed to a better coffee tree development, observed mainly in the treatments using the Crotalaria and Guandu species.